Kinerja Bapemas dan KB Kota Surabaya berdasarkan Analisis Perubahan Rencana Kerja dan Laporan Kinerja - Deby Indah Permatasari (Universitas Airlangga, 2017)
The average population density of Surabaya is 9.002 people per km2 in 2009. The over population density is potential to occuring problem in health, education, social and economics. To solve that problems, government formed The Empowerment Society and Family Planning(Bapemas dan KB) in Surabaya City. Bapemas dan KB of Surabaya should compute and analyze the performance achievement to attain the optimum performance. This research was to analyse The Performance Achievement based on Performance Planning Document and Performance Planning Amendment compares with Performance Report to solve the performance of workers. This reaserch is observational descriptive research which is held in Sub Area Family Planning Bapemas dan KB Surabaya. The Observation studied The Performance Planning Document and Performance Planning Amendment that compares to Performance Report. The Indepth Interview was in Administrative unit, Head of the Sub-Division, and Head of Division Prosperous Family and Family Planning “Bapemas dan KB” Surabaya. Data Analysis Method using Assesment of Performance Indicators Target that measured by Performance Measurement Form, Self Assesment, and Budget Realization. Performance achievement result were: Family Planning Founding Program was 61,58%; Contraceptiption Service Provision for Poor Family Program was 97,17%; in Family Planning Infrastructure Program was 200%. Keywords:performance, performance report, family planning, program.